COMMUNITY OF CHILDREN INMATES AND ASSISTANCE SYSTEM IN THE PENITENTIARY: The Impact of Child Social System to the Assistance Process at Kutoarjo Children Penitentiary - Utari, Indah Sri (Universitas Negeri Semarang (UNNES), 2017)
The community of inmates children as a unique and unique social system is difficult to understand when viewed only from the outside, so it is necessary to systematically attempt to know the values, norms, relationships, and objectives-through where and with what they are living, and understand both their own experiences and the world in which they liveThe situational system of the inmates children as human beings (although in this case is the child) to be fostered, is one of the important elements in the whole process of assistance in the Penitentiary is no exception to the Children Penitentiary in Kutoarjo. The entire penitentiary system design, from the assistance program, the assistance mechanism, and the assistance implementation, is actually determined by the circumstances and the reality of the people who are to be fostered, the inmates.The reality of the children inmates who are always on the